Primary Localizatıon of a Hydatid Cyst in the Quadriceps Femoris Muscle - Cinpolat, Ozgur; Piskin, Turgut; Isik, Burak; Sogutlu, Gokhan; Olmez, Aydemir; Yilmaz, Sezai; Kirimlioglu, Vedat (Annals of Medical Research, 2021)
None